Building resilience in teacher education: An evidenced informed framework. (February 2016) - Mansfield, Caroline F.; Beltman, Susan; Broadley, Tania; Weatherby-Fell, Noelene
Abstract: This paper proposes a framework for building resilience in teacher education. The framework is informed by a focused review of relevant literature to determine factors that may be addressed in teacher education to support teacher resilience and ways in which this may occur. Findings show that personal and contextual resources along with use of particular strategies all contribute to resilience outcomes and that many of these can be developed in teacher education. Using these findings, a comprehensive resilience framework is proposed with five overarching themes - understanding resilience, relationships, wellbeing, motivation and emotions. Implementation possibilities are discussed. Highlights: Presents an evidence-based framework for building resilience in teacher education. Reviews literature over 15 years identifying key factors associated with teacher resilience. Identifies personal and contextual resources, strategies and outcomes of the resilience process. Discusses implementation possibilities in teacher education.